Effect of fiber orientation on energy absorption characteristics of glass cloth/epoxy composite tubes under axial quasi-static and impact crushing condition. (November 2016) - Hu, Dayong; Zhang, Chong; Ma, Xiaobing; Song, Bin
Abstract: The collapse characteristics and energy absorption capability of composite tubes made of 759/5224 woven glass cloth/epoxy with different fiber orientations were studied in the present article under axial quasi-static and impact crushing condition. The effects of fiber orientation and loading condition on the crushing modes and energy absorption capability were discussed in detail. The fiber orientation could be found to have significant influences on energy absorption performance. Based on results, the energy absorption capability could be improved by selecting proper fiber orientation. The energy absorption capability in impact crushing tests could be found to be slightly lower than that in quasi-static crushing tests.